TYPOLOGICAL STATUS OF COMPLEX SENTENCES WITH AN ADVERBIAL COMPONENT OF FINALITY IN LANGUAGES OF DIFFERENT SYSTEMS (Scientific journal of the Fergana State University, 2024)
The article touches upon one of the least investigated problems of modern linguistics - typology of the hypotaxemes(complex sentence) with an adverbial component of purpose in more than one hundred languages of the world that gave the author the possibility of disclosing the their isomorphic and allomorphic features and revealing their universal features.